How to stand up to a dictator : the fight for our future - Ressa, Maria (Harper, an imprint of HarperCollinsPublishers, 2022)
From the recipient of the 2021 Nobel Peace Prize, an impassioned and inspiring memoir of a career spent holding power to account.